Masticatory and Neck Muscles’ Isometric Endurance and Their Relation to Upper Limb Isometric Grip Strength in Sport Climbers—Preliminary Investigation - Michał Baszczowski; Aleksandra Dolina; Magdalena Zawadka; Michał Ginszt; Adam Czarnecki; Agata Ginszt; Piotr Gawda (Medicina)
Background and Objectives: Sport climbing’s popularity has grown with its inclusion in the Olympics and increased accessibility. Understanding the relationship between hand dominance, grip strength, endurance, and the involvement of masticatory and neck muscles can provide valuable insights into the neuromuscular adaptations specific to sport climbing, potentially aiding performance optimization and injury prevention in intermediate and advanced climbers. This study analyzes if the dominant hand has greater isometric endurance and isometric manual grip strength parameters than the non-dominant one and examines its relation to the masticatory and neck muscles in intermediate and advanced sport climbers. Materials and Methods: The study was conducted on 41 participants who were divided into two groups according to the IRCRA classification. A level 2 (Lv2) group consisting of 18 climbers and a level 3 (Lv3) group consisting of 23 climbers were identified. First, isometric manual grip strength and isometric endurance were measured using a dynamometer following the protocol of the first three and the last three repetitions (PC3) and the first six and the last six repetitions (PC6). Next, masticatory and neck muscle activity was assessed using surface electromyography, following the same protocol. Results: Greater activity of the temporalis muscle was observed on the non-dominant side in the advanced climber’s group (p = 0.045). The decrease in bioelectric activity was lower on the dominant side in group Lv3 compared to Lv2. In intermediate climbers, the bioelectrical activity of the masseter muscles in PC3 was greater on the non-dominant side, and in PC6, was greater on the dominant side. The digastric muscles showed a greater decrease in isometric endurance on the non-dominant side. Conclusions: Advanced climbers demonstrated greater isometric endurance and isometric manual grip strength parameters in both dominant and non-dominant hands compared to intermediate climbers. The masticatory muscles exhibited higher electromyographic activity on the non-dominant side in the masseter muscles and higher electromyographic activity on the dominant side in the temporalis muscles and digastric muscles.